Influence of Comorbidities on Outcome of Severe Pneumonia among Children Aged 2-59 Months Admitted in Bondo Sub County Hospital Paediatric Ward - Akoo, Timon Kwach (JOOUST, 2023)
Severe pneumonia is defined by a history of cough or difficulty in breathing and any danger sign like; oxygen saturation <90%, Cyanosis, Inability to drink or breast feed, grunting and altered level of consciousness (World Health Organization, 2019). Pneumonia is the leading infectious cause of death among children worldwide. 740,180 children under the age of five died from severe pneumonia in the year 2019, accounting for 14% of all pediatric fatalities among this age group and 22% of all deaths among children aged 1 to 5 years. More than 95% of all new cases of pneumonia in children less than 5 years occur in developing countries due to the increased prevalence of under nutrition. Studies have shown that severe acute malnutrition is an independent predictor of mortality in patients of severe pneumonia, this can be used to identify cases at increased risk of mortality among this group and measures taken to reduce the cases of severe acute malnutrition will further decrease the mortality. Clinical and epidemiological studies reported evidence that maternal HIV infection can deeply affect the maternal/fetal unit, interfering with the immunomodulatory factors which shape immune maturation in fetuses. This puts HIV exposed uninfected children at risk of severe infections like severe pneumonia. Other comorbidities such as sickle cell disease also puts a child at risk of developing severe infections caused by encapsulated organisms like pneumococcal organism due to auto-splenectomy. The role of HIV infection as a comorbidity leading to immunodeficiency cannot be underestimated in children with severe pneumonia. The specific objectives of this study were to determine the prevalence of comorbidities related to severe pneumonia among children aged 2-59 months admitted in Bondo sub county hospital, to determine the outcome of severe pneumonia with specific comorbidities among children aged 2-59 months admitted in Bondo sub county hospital and to determine the influence of nutritional status on outcome of severe pneumonia with specific comorbidities among children aged 2-59 months admitted in Bondo sub county hospital. 141 children of either gender from 2– 59 months of age with the clinical diagnosis of severe pneumonia, made according to integrated management of childhood illnesses (IMCI) guidelines were recruited into the study. The study employed a retrospective cross-sectional study design where secondary data was extracted from the inpatient files of those admitted as from July 2017 to June 2019. The study employed a systematic sampling technique. The samples size was 141 and data was collected using a structured observation checklist from within a period of two months after obtaining ethical approval for the study. Data was analyzed using descriptive and inferential statistics in the statistical package for the social sciences V24 (SPSS V24). The findings showed that 44.7% (63/141) of the children had severe pneumonia and at least one comorbidity. It was further noted that a child admitted to the hospital with severe pneumonia and comorbidity had six times increased risk of death compared to a child with severe pneumonia o nly [OR 6.06 (1.32-27.78) P value 0.02]. Specifically, there is four times increased risk of death among HIV-exposed uninfected children [OR 3.92 95% CI (1.18-13.04) P = 0.026] and the risk of death increased six times when the child was both HIV-exposed uninfected and malnourished [OR 6.02 95% CI (1.61-22.58) P = 0.008]. Therefore, the study concludes that there is a significant influence of nutritional status on the outcome of severe pneumonia and rejects the null hypothesis. The findings of this study would inform policy makers on the need to review pneumococcal pneumonia immunization schedule among children with severe acute malnutrition and their HIV exposed uninfected counterparts. It therefore recommends that health care providers should intensively examine children with malnutrition and HIV exposed uninfected (HEU) so as to rule out pneumonia or detect it early enough before it gets severe. Lastly, community health volunteers should be empowered with knowledge on nutritional counseling of the community members to reduce the burden of malnutrition among these children at the household level.
Keywords: Comorbidities; Pneumonia